(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Marketing Channels of Organic White Rice in Subak Jatiluwih, Jatiluwih Village, Penebel District, Tabanan Regency. Organic white rice is rice produced by an organic process without the use of pesticides from the initial seed planting to processing into rice. organic white rice, namely rice that does not contain harmful chemicals. Subak Jatiluwih is used as the main attraction in the development of the Jatiluwih Tourism Village with its natural beauty in the form of wide terraced rice fields and terraces so that it becomes one of the best tourist destinations in Bali. This study aims to determine the marketing channel used by farmers and marketing agencies for organic white rice in Subak Jatiluwih and the efficiency of the marketing channel for organic white rice based on marketing costs and selling prices obtained by marketing agencies. The research location was conducted in Subak Jatiluwih, Jatiluwih Village, Penebel District, Tabanan Regency. The data used in this study are primary data and secondary data. Qualitative data analysis methods are used to determine existing marketing channels and quantitative analysis methods to calculate Farmer’s share marketing margins, and efficiency. The results of this study are three marketing channels for organic white rice, namely marketing channel I farmer to consumer, marketing channel II farmer to collectors then to retailers then to consumers, and marketing channel III farmers to online retailers after that to consumers. On the marketing channel I the marketing margin is Rp.0 and the farmer’s share is 100%. On the marketing channel II the marketing margin is 10,000 thousand and the farmer’s share is 50% said to be more efficient than the marketing channel III. Based on the results of this study, it is hoped that farmers will sell organic white rice on channel I but still maintain good relations on marketing channels II and marketing channels III to expand the reach of farmers in marketing their organic white rice.